A reményteljes múlt és a választott örökség - Balázs SIBA (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2021)
The Hopeful Past and the Chosen Inheritance. Living in a given historical place and time, we inherit stories, and by filtering them through our lives and experiences, we transform them into parts of our own story. In this article, we examine the relatedness between our stories and the story of the Kingdom of God. The metanarrative of the God–human relationship is a continuously changing system with permanent perspectives, a tradition that offers a system of rules to Christian communities and, on the other hand, interprets the individual’s life and integrates it into the history of salvation. Christian life appears in front of us as a study process, a search, but it is hope as well. We should not forget about the eschatological dimension of Christian faith: the hope in God, who saved us in the past and will hold us in the future.